2021
DOI: 10.1021/acs.estlett.1c00730
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Lockdowns Afford the First Satellite-Based Confirmation That Vehicles Are an Under-recognized Source of Urban NH3 Pollution in Los Angeles

Abstract: In situ measurements have suggested vehicle emissions may dominate agricultural sources of NH 3 in many cities, which is alarming given the potential for urban NH 3 to significantly increase human exposure to ambient particulate matter. However, confirmation of the prevalence of vehicle NH 3 throughout a city has been challenging because of mixing with agricultural sources, and the latter are thus routinely assumed to dominate.Here we report vehicle NH 3 emissions based on TROPOMI NO 2 and CrIS NH 3 (0.152 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…In contrast, other studies have suggested that vehicle emissions are relatively unimportant for urban regions and instead have found evidence for significant local and transported emissions due to temperature-dependent volatilization sources (Hu et al, 2014;Yao et al, 2013;Nowak et al, 2006). Recent satellite observations, taking advantage of the COVID-19 lockdown period, have for the first time confirmed vehicle emissions as a significant localized source of NH 3 in an urban region (Cao et al, 2021). However, quantifying the contribution of local urban NH 3 emissions to the urban background is complex as it is coupled to meteorological parameters that influence NH 3 and particulate ammonium (pNH + 4 ) partitioning, mixing/dispersion of local emissions, and contributions via long-range transport from agricultural regions (Meng et al, 2011;Walker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies have suggested that vehicle emissions are relatively unimportant for urban regions and instead have found evidence for significant local and transported emissions due to temperature-dependent volatilization sources (Hu et al, 2014;Yao et al, 2013;Nowak et al, 2006). Recent satellite observations, taking advantage of the COVID-19 lockdown period, have for the first time confirmed vehicle emissions as a significant localized source of NH 3 in an urban region (Cao et al, 2021). However, quantifying the contribution of local urban NH 3 emissions to the urban background is complex as it is coupled to meteorological parameters that influence NH 3 and particulate ammonium (pNH + 4 ) partitioning, mixing/dispersion of local emissions, and contributions via long-range transport from agricultural regions (Meng et al, 2011;Walker et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2g) the match deteriorates with some provinces showing large underestimations while others overestimate, which points to a geographic misattribution of the emissions in the inventory. Some of the stronger point source-like differences can be related to large megacities such as Mexico City, Santiago and Karachi, with emissions potentially being related to a combination of urban anthropogenic sources such as emissions from vehicles, coal and wood stoves and industrial activities 19,24,47,48 . Industrial sources such as fertiliser and soda-ash plants are also observed, for example throughout Russia and north-western China that match up with point source locations reported in earlier studies reporting on single sources 19,20,49 and are typically underreported in emission inventories.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other studies have suggested that vehicle emissions are relatively unimportant for urban regions and instead have found evidence for significant local and transported emissions due to temperature-dependent volatilization sources (Hu et al, 2014;Yao et al, 2013;Nowak et al, 2006). Recent satellite observations, taking advantage of the COVID-19 lockdown period, have for the first time confirmed vehicle emissions as a significant localized source of NH3 in an urban region (Cao et al, 2021). However, quantifying the contribution of local urban NH3 emissions to the urban background is complex as it is coupled to meteorological https://doi.org/10.5194/acp-2022-419 Preprint.…”
Section: Introductionmentioning
confidence: 94%